KOKAMI: The innovation of learning impuls and momentum in senior high school - Siti Nurfadilah; Tatan Zenal Mutakin (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Learning using learning media is very helpful for students in understanding the subject matter. However, many learning media are not yet able to involve students actively involved in learning. The purpose of this research is to develop and implement KOKAMI learning media in the learning process. The results showed that the media developed is very feasible and able to improve students' learning outcomes, critical thinking skills and improve students' learning activities. This learning medium is very suitable to be applied in the implementation of the current curriculum.